White spot lesion remineralization by sugar-free chewing gum containing bio-available calcium and fluoride: A double-blind randomized controlled trial. (November 2016) - Sugiura, Miho; Kitasako, Yuichi; Sadr, Alireza; Shimada, Yasushi; Sumi, Yasunori; Tagami, Junji
Abstract: Objectives: To assess the effect of chewing gum containing phosphoryl oligosaccharides of calcium (POs-Ca) and fluoride on white spot lesion (WSL) remineralization in comparison with POs-Ca or placebo (control) chewing gums, in double- blind, randomized, controlled trial. Methods: Thirty-seven healthy subjects, who had at least one WSL, with an ICDAS score of 2 or 1, were recruited for this study. The subjects were randomly divided into three groups (control, POs-Ca, POs-Ca + F) and chewed two slabs of each gum three times every day for 3 months. WSLs were assessed using ICDAS criteria and optical boundary depth (BD) by optical coherence tomography (OCT) system at a monthly recall. Data were analyzed by Wilcoxon rank-sum test and Wilcoxon signed rank test with Bonferroni corrections at 0.05 significance level. Results: Visual score changes from ICDAS score 2 to score 1 over the course of the study were observed; control (30%), POs-Ca (48%) and POs-Ca + F (45%). Unlike the control gum, chewing POs-Ca and POs-Ca + F gums resulted in significant changes in the mean value of BD over the 3 months course of the study (p < 0.05). There was a significant difference in mean value of BD after first month between POs-Ca + F and control groups (p < 0.05). Conclusions: This study highlighted the importance of calcium and fluoride ion bioavailability in the reinforcement of demineralized enamel lesions by chewing gums. Furthermore, adding fluoride to POs-Ca might speed up the remineralization progress on natural WSL.